The factors that influence price of the bitcoin from 2013 to 2017 / Siti Nur'atikah Jamalludin - Jamalludin, Siti Nur'atikah (Faculty of Business and Management, 2018)
The most popular cryptocurrency today is bitcoin. It starts with a fascinating idea as the first decentralized digital currency that their system can works without any third party financial intention. The bitcoin price at the start is only a few cents and now it hits thousands. As at 31 December 2017, bitcoin was worth around USD 13215.574. This project paper aims to investigate the factors that influence price of the bitcoin from 2013 to 2017 by Multiple Regression analysis.